From evolution to discourse: Key conceptual debates in the history and study of traumatic stress - Eagle, Gillian (PINS-Psychology in Society, 2025)
The study of traumatic stress has a long and rich history, drawing upon many of the major strands of thinking in the discipline of psychology. The article highlights three important sets of debates arising out of the study of traumatic stress, exploring how these debates reflect ongoing dilemmas in the study of extreme stressors and the formulation of their impact on individuals and groups. The three key areas selected for discussion are firstly, the origins or causes of traumatic stress, secondly, understandings of the mechanisms by which people are theorised to become traumatised, and thirdly, the political, cultural and discursive positioning of the construct of traumatic stress. It is argued that research and writing on traumatic stress is reflective of broader tensions in psychology related to addressing concerns about scientific credibility, models of personhood and the social location of human subjects, amongst other issues. The need for integrative, cross-disciplinary and ever evolving scholarship in the area is highlighted.